Conceptual and Categorical Framework in the Sphere of Prevention of Child Neglect and Juvenile Delinquency: Comparative Analysis - ILGOVA, Ekaterina; DORODONOVA, Natalia; GORBACHEV, Mikhail; EVSTIFEEVA, Ekaterina; SMAGINA, Tamara (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020DO - 10.14505//jarle.v11.1(47).08, 2020)
In the legislative practice of foreign countries, the normative definitions regulating an activity in the field of prevention of child neglect and juvenile delinquency are set forth in both regulatory and conservatory legislation. International legislation in this field imposes an obligation on states to bring domestic regulations into line with international standards. However, a large number of legal categories in the sphere of prevention of child neglect and juvenile delinquency have contributed to their consolidation in various branches of law that could not affect an emergence of problems in the effective regulation and protection of social relations arising in this area. The aim of this research is to prepare a theoretical basis of the legal grounds and to reveal the effectiveness of implementation of conceptual and categorical framework in the field of prevention of child neglect and juvenile delinquency. The analysis of legislation is used with dialectical method as a universal cognition method in combination with general scientific and private scientific methods as dogmatic (formal and logical) and comparative legal, formal legal methods. It is concluded that the definitions used in regulations of the former Soviet republics are the most similar. In English-speaking countries some legal concepts in the field of prevention of child neglect and juvenile delinquency are not clearly similar. The result of the research has shown that regulations are characterized by their own content or by their own terminology used in a particular country. Despite the differences in definitions states generally follow a policy of ensuring minors’ rights and freedoms. The article specifies a general conception of interrelation between international and domestic legislation in the field of prevention of child neglect and juvenile delinquency.